2020
DOI: 10.15441/ceem.19.022
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the effects of prehospital advanced airway management on outcomes of patients with out-of-hospital cardiac arrest

Abstract: Objective To investigate variations in the effects of prehospital advanced airway management (AAM) on outcomes of out-of-hospital cardiac arrest (OHCA) patients according to regional emergency medical service (EMS) systems in four Asian cities. Methods We enrolled adult patients with EMS-treated OHCA of presumed cardiac origin between 2012 and 2014 from Osaka (Japan), Seoul (Republic of Korea), Singapore (Singapore), and Taipei (Taiwan). The main exposure variable was prehospital AAM. The primary endpoint was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…Differences in the style of pre-hospital rescue service and hospital transport times in countries and regions may have contributed to the variability in results. 12 In the present study, the effect of interruption of chest compressions by tracheal intubation or supraglottic airway devices was not significant, and it was proved that interruption of chest compressions by asynchronous ventilation using advanced airway devices had a more favorable effect on CCF in prehospital rescue activities in Japan.…”
Section: Discussionmentioning
confidence: 44%
“…Differences in the style of pre-hospital rescue service and hospital transport times in countries and regions may have contributed to the variability in results. 12 In the present study, the effect of interruption of chest compressions by tracheal intubation or supraglottic airway devices was not significant, and it was proved that interruption of chest compressions by asynchronous ventilation using advanced airway devices had a more favorable effect on CCF in prehospital rescue activities in Japan.…”
Section: Discussionmentioning
confidence: 44%
“…Another study demonstrated the significant regional variations in prehospital AAM and their effects on the outcomes of OHCA patients across four Asian EMS systems. 24 On the other hand, even in Japan, the AAM rate ranged from 27.2% to 62.1% after dividing Japan into seven geographic regions. 25 These findings can be interpreted as that the policies or strategies for prehospital AAM markedly differ according to region in Japan.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Only 19.2% of patients received AAM in South Korea. 27 The characteristics of pOHCA can affect the outcome; unlike during cardiac cause arrest, ventricular arrhythmia is low, and rapid respiratory support is required. 14 28 It can be assumed that pOHCA is related to the damage induced by the poisons that cause hypoxia in apnoea and hypercapnia; therefore, rapid CPR is needed.…”
Section: Discussionmentioning
confidence: 99%
“…These factors may be influenced by prehospital care provided by EMS. The EMS system shows variability based on regional infrastructure, which may lead to differences in the outcomes of EMS-treated OHCAs; when an OHCA occurs in the US, an average of 80% or more of patients receive advanced airway management (AAM),26 but in some parts of Asia, AAM implementation by EMS is less than 50% 27. Only 19.2% of patients received AAM in South Korea 27.…”
Section: Discussionmentioning
confidence: 99%